1991
DOI: 10.2190/cf72-vuqe-34u9-a5uc
|View full text |Cite
|
Sign up to set email alerts
|

Apathetic Hyperthyroidism in Middle Age

Abstract: Apathetic hyperthyroidism was first described in the medical literature by Lahey in 1931. It is a form of hyperthyroidism found principally in the elderly population. In this disorder the usual hyperkinetic presentation of thyrotoxicosis is replaced by apathy and inactivity, often leading to an erroneous psychiatric diagnosis. Although there is a paucity of literature on apathetic hyperthyroidism, it has been described in the elderly and as an extremely rare complication of hyperthyroid disorder in children. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…2 Although many of the somatic symptoms of anxiety (such as tachycardia and tremor) may be caused by increased peripheral sympathetic tone secondary to thyrotoxicosis, several studies have suggested that additional psychiatric and cognitive impairments are also seen in hyperthyroid patients. [3][4][5][6][7][8][9][10] These findings suggest a possible central effect, either due to alterations of brain thyroid hormone homeostasis or, perhaps, to autoimmune involvement in the brain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Although many of the somatic symptoms of anxiety (such as tachycardia and tremor) may be caused by increased peripheral sympathetic tone secondary to thyrotoxicosis, several studies have suggested that additional psychiatric and cognitive impairments are also seen in hyperthyroid patients. [3][4][5][6][7][8][9][10] These findings suggest a possible central effect, either due to alterations of brain thyroid hormone homeostasis or, perhaps, to autoimmune involvement in the brain.…”
mentioning
confidence: 99%
“…Furthermore, although clinical endocrinologists acknowledge that psychiatric and cognitive complaints are common in patients with Graves' disease, there have been no studies addressing the possible impact of these complaints on initial diagnosis and treatment. Finally, it is unclear whether the neuropsychiatric difficulties in Graves' disease follow a course parallel to the resolution of thyrotoxicosis [5][6][7][8][9][10][11] or remain after euthyroidism has been achieved. [9][10][11][12] In this report, we present the results of a survey of the patient membership of the National Graves' Disease Foundation.…”
mentioning
confidence: 99%
“…This form of hyperthyroidism is known as "Apathetic" or non-activated hyperthyroidism [4,5]. It is principally found in the elderly population and the usual hyperkinetic presentation of thyrotoxicosis is replaced by apathy and inactivity, making it difficult to diagnose [6]. Untreated hyperthyroid state increases risks of angina, heart failure and atrial fibrillation in the elderly [4].…”
Section: Differential Diagnoses Were Considered Asmentioning
confidence: 99%
“…In contrast to the hyperkinetic appearance of typical hyperthyroidism, the main clinical features include apathy and inactivity. Several case reports and reviews have complemented the description of apathetic thyrotoxicosis 3–7 . However, apathy in thyroid storm has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%